WZ SGE STARS - Pavlenko, E. P. (Одеські астрономічні публікації, 2007)
The WZ Sge type stars is a rare subclass of the cataclysmic variables (CVs). It possesses the properties of both dwarf novae and recurrent novae. The WZ Sge stars have the shortest orbital periods (typically 80 - 90 minutes) known among the dwarf novae, and the long (decades) recurrent time of outbursts never displayed by the dwarf novae but that is typical for the recurrent novae. At the same time the WZ Sge stars show their own unique peculiarities and are the promising objects for search for the brown dwarfs in close binaries. The brief review of the main characters of the known WZ Sge stars is given including the last results of the newly discovered and investigated binaries of this type.